Intestinal Humoral Immune Response and Resistance to Salmonella Challenge of Progeny from Breeders Vaccinated with Killed Antigen - Bailey, J.S.; Rolon, A.; Hofacre, C.L.; Holt, P.S.; Wilson, J.L.; Cosby, D.E.; Richardson, L.J.; Cox, N.A. (International Journal of Poultry Science, 2007)
Salmonella vaccination programs using killed bacterins in breeders and live auxotrophic-strain vaccines early in the life of their progeny have gained popularity in today`s poultry industry. In this study we evaluated the intestinal humoral immune response to a live auxotrophic vaccine used on hatchlings with and without maternal antibody and related this response to challenge with a blend of two antibiotic-resistant Salmonella marker strains. Forty wk-old ISA Brown® (Institute de Selection Animale, France) breeders from a Salmonella-free flock were vaccinated twice at a three wk interval with commercially-prepared autogenous trivalent bacterin, serogroups B, C and D1 (Lohmann Animal Health International, Gainesville, GA), or a serovar Enteritidis bacterin (Fort Dodge Animal Health Inc, Overland Park, KS). Half of the progeny from these treatments (hatched from eggs laid 3 wks after second bacterin dose) were given a live Salmonella serovar Typhimurium (LiveST) mutant vaccine (Fort Dodge Animal Health Inc, Overland Park, KS), by coarse spray on arrival in the brooding premises. On days 3, 13 and 34, intestinal immunoglobulins (Ig) A and G were sampled and measured on enzyme-linked immunosorbent assay plates coated with Salmonella serovars Enteritidis (SELPS) or Typhimurium (STLPS) Lipopolysaccharide. On the same days, a second group of birds was challenged with a blend of antibiotic-resistant serovars Enteritidis and Typhimurium strains. Cecal and composite liver-heart-spleen samples obtained 7 days post-challenge were cultured and colonies enumerated. Maternal IgG observed up to 13 days had no effect on subsequent LiveST-stimulated antibody production. No protective effect of maternal antibody was demonstrated, except when combined with LiveST given to the progeny. Killed vaccines delivered to the breeders combined with a live vaccine delivered to the progeny resulted in reduced invasiveness after challenge, as shown by a reduction in liver-heart-spleen Salmonella counts. One dose of LiveST enhanced intestinal IgG [Optical Densities (OD) >0.576] up to 34 days when measured on STLPS, but only to 13 days when measured on SELPS, with titers decreasing with age. Increased IgA was observed only at 13 days. Three and 13 but not 34 days bacterial counts were decreased by the live ST vaccine treatment, for both cecal (1.05 and 1.09 log10) and liver-heart-spleen (0.32 and 0.06 log10) samples, indicating that a second dose might be necessary for prolonged protection. The protective effect of the live vaccine, but not of maternal IgG, leads us to hypothesize that protection might be due to stimulation of cell-mediated intestinal immunity and/or a competitive exclusion effect of the LiveST vaccine. Reduction but not elimination of Salmonella colonization by vaccination highlights the importance of vaccines as complementary tools and not substitutes of integral biosecurity programs to control Salmonella in poultry.